Newcomers Learning Religious Ritual: Legitimate Peripheral Participation in an Orthodox Worshipping Community - Kupari, Helena; Utriainen, Terhi (Approaching Religion, 2024)
In this article, we explore the learning of newcomers in a religious community through a micro-sociological approach, making use of Jean Lave and Etienne Wenger’s (1991) notion of “legitimate peripheral participation” to conceptualize initial stages of inclusion and involvement in social practice. Our case study concerns Orthodox Christianity and is based on material gathered through fieldwork in a course targeting potential new members organized by a Finnish Orthodox parish. In the analysis, we inquire into how beginners learn skilful participation in Orthodox liturgical life, and specifically embodied ritual conduct. This learning takes place primarily through participation in real-life divine services. The article highlights challenges faced by beginners in acquiring the embodied repertoire of Orthodox ritual, including adapting to the artistic use of ritual gestures, and negotiating the meanings produced through them. Furthermore, it also illustrates how nuanced dynamics between newcomers and old-timers influence the learning process.